True Arterial Stiffness Does Not Change between Dialysis Sessions during 1 Week in Outpatients on Intermitted Hemodialysis - Alexander Reshetnik; Daniel Wrobel; Georg Wirtz; Markus Tölle; Kai-Uwe Eckardt; Markus van der Giet (Karger Publishers, 2019)
Introduction: End-stage renal disease (ESRD) is associated with exponentially elevated cardiovascular mortality. Arterial stiffness (AS) - usually expressed with pulse wave velocity (PWV) - is an established independent predictor of cardiovascular risk beyond the traditional risk factors. Higher PWV values are frequently observed in patients with ESRD. Due to the intrinsic physiologic relationship between PWV and prevailing arterial pressure, PWV can change without relevant changes in the arterial wall structure, and thus an individual pressure-independent expression of PWV is essential. Methods: The study is a single-center observational study. Repeated measurements of blood pressure (BP) and pulse wave analysis were performed during each dialysis session of 1 week. Aortic PWV was then adjusted to 120 mm Hg central systolic BP (PWV120) based on individually determined relationship. PWV120 values were compared between single sessions. Calculation of the PWV120 was performed retrospectively. Results: Fifty-four subjects were included, 61.1% of whom were male. The median age was 75.5 years, and median dialysis vintage was 33.1 months. Mean systolic/diastolic BP was 121.4/70.5 mm Hg, and the median heart rate was 64.6 beats/min. Mean PWV was 10.9 m/s, and mean PWV120 was 11.3 m/s. PWV120 did not change across single dialysis session during 1 week, while systolic, diastolic BP, PWV, and ultrafiltration volume differed significantly. Discussion/Conclusions: Our data suggest that true AS does not change in the short-term course in dialysis patients. The observed changes in PWV are rather associated with BP change due to intrinsic pressure dependence. Our analytical approach represents a novel method for this purpose, which is easy in performance and also applicable for large interventional trials and clinical practice.